Prevalence and risk factors with type 2 diabetes mellitus among young adults at a district hospital in Trujillo, Peru - Gandij Yamil Melendez-Medina (TUMI Health Sciences Research, 2026)
Introduction: Type 2 diabetes mellitus (T2DM) can occur early in adulthood and coexist with metabolic abnormalities that increase the burden of disease in this population. Objective: To determine the prevalence of T2DM and the risk factors associated with the disease among young adults treated at a district hospital in Trujillo, Peru, between 2020 and 2024. Methods: An observational, retrospective, analytical, cross-sectional study was conducted among adults aged 18 to 30 years. Prevalence was estimated from 1,258 clinical records, while the analysis of risk factors was performed using 98 medical records. Age, sex, dyslipidemia, obesity, hypertension, and family history of T2DM were evaluated. Associations were assessed using the chi-square test and odds ratios, with a significance level of p < 0.05. Results: The prevalence of T2DM was 3% (39/1,258). In the analysis of 98 medical records, dyslipidemia (OR = 3.50; p = 0.012), obesity (OR = 3.80; p = 0.006), hypertension (OR = 3.45; p = 0.039), and family history of T2DM (OR = 3.33; p = 0.023) were significantly associated with T2DM. No significant associations were observed with age (p = 0.17) or sex (OR = 1.09; p = 0.85). Conclusions: Among the young adults studied, the prevalence of T2DM was 3%. Dyslipidemia, obesity, hypertension, and family history were identified as statistically significant risk factors associated with T2DM.